1995
DOI: 10.1088/0029-5515/35/7/i06
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic theory of the anomalous transport of superthermal electrons in toroidal devices

Abstract: An investigation has been made of the behaviour of fast electrons in toroidal discharges. The kinetic equation, describing the evolution of the fast particle distribution has been derived and analysed. A semianalytical solution of the kinetic equation has been obtained in the superthermal energy region. The external electric field, turbulence, the non-uniformity of the mean magnetic field and collisions are shown to be important factors affecting the distribution function. The role of the ambipolar electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, the effect of turbulence on the suprathermal electron distribution has been analysed in Ref. [25] using a special diffusion operator in configuration and velocity space. Moreover, attention has been drawn recently to the fact that collisionless diffusion of particles across the magnetic field can take place when particles are accelerated along the magnetic field lines [26, 271.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effect of turbulence on the suprathermal electron distribution has been analysed in Ref. [25] using a special diffusion operator in configuration and velocity space. Moreover, attention has been drawn recently to the fact that collisionless diffusion of particles across the magnetic field can take place when particles are accelerated along the magnetic field lines [26, 271.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, high energy particles exist due to the effect of external forces acting on the space environment plasmas. Gurevich et al [19] investigated the behaviour of fast or superthermal electrons by deriving the kinetic equation and demonstrated the strong influence of the density profile on the diffusion of fast particles. Lu et al [20] studied the presence of superthermal electrons in the space plasma and observed the variation of indices of the power law distribution in the magnetosheath.…”
Section: Introductionmentioning
confidence: 99%